The 2nd International Cell Death Research Congress 2018
DOI: 10.3390/proceedings2251548
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Bcl-2 and Bax Protein Levels for Determining the Apoptotic Changes in Placentas with Gestational Diabetes and Preeclampsia

Abstract: Anti-apoptotic Bcl-2 and proapoptotic Bax genes are the most significant genes that are involved in the regulation of apoptosis. Abnormal apoptotic activity in preeclampsia and gestational diabetes is caused by dysregulation of these genes. In this study; we examined Bcl-2 and Bax protein expressions using immunohistochemical techniques in human placental tissue samples from cases of gestational diabetes (n: 20) and preeclampsia (n: 20). It was observed that Bax expression showed positive reaction compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Abnormalities in the expression of Bax protein, which is involved in apoptosis, are associated with some pathological placental changes (24). In a study, Bax protein was discovered to be a good indicator of apoptotic alterations in placentas with gestational diabetes and preeclampsia (50). In another study, it was reported that the Bax gene could be responsible for pregnancy loss, and variation of this gene would be useful in the evaluation of recurrent pregnancy loss (51).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in the expression of Bax protein, which is involved in apoptosis, are associated with some pathological placental changes (24). In a study, Bax protein was discovered to be a good indicator of apoptotic alterations in placentas with gestational diabetes and preeclampsia (50). In another study, it was reported that the Bax gene could be responsible for pregnancy loss, and variation of this gene would be useful in the evaluation of recurrent pregnancy loss (51).…”
Section: Discussionmentioning
confidence: 99%
“…The Bcl-2 and Bax genes are the most important genes that control and regulate apoptosis. It was found that the Bcl-2 and Bax genes act in concert to maintain programmed cell death in the placenta [ 45 ]. Abnormal apoptotic activity in the placenta may be caused by a violation of the regulation of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Placentas with both preeclampsia and gestational diabetes have a favorable response to the BAX protein. Sgarbosa et al investigated BCL-2 expression in normoglycemic and diabetic placentas and found that hyperglycemic placentas had lower levels of the protein, which might indicate diseases that cause apoptosis [244]. Solanesol (SNL) alters apoptotic markers (caspase-3, BAX, and BCL-2), reduced TNF-, IL-1 [232] MiRNAs have been identified as essential regulators of beta cell growth, glucose-stimulated insulin secretion (GSIS), and beta cell malfunction in several investigations [245][250] [251].…”
Section: Diabetesmentioning
confidence: 99%